Efficacy of curcumin in the management of oral submucous fibrosis - An intervention study - K Namratha; Prashanth Shenoy; Laxmikanth Chatra; Prasanna Kumar Rao; Rachana V Prabhu (Wolters Kluwer Medknow Publications, 2023)
Background and Objective: Oral submucous fibrosis (OSMF), a chronic, inflammatory, and potentially malignant disorder of the oral cavity, has been linked to the chewing of arecanuts. Antioxidants and quitting habits ought to both be incorporated into OSMF therapeutic interventions regimens. Current study aimed to determine curcumin's efficacy as an antioxidant in the management of OSMF. Materials and Methods: In this intervention study, 42 participants with OSMF were allocated into three groups. Group A received curcumin; group B received intralesional steroid injections; and group C received neither treatment (placebo group). For three months, groups A and B received twice-daily doses of 400 mg of curcumin each, while group C received twice-daily doses of placebo capsules. Group B also received biweekly intralesional steroid injections of 4 mg/ml of betamethasone. Data were analyzed using statistical tests. Results: After receiving interventions, group B patients showed clinically significant improvements in mouth opening. Both Group A and B reported a burning sensation reduction that was statistically significant. Statistically, greater improvement in mouth opening and a decrease in burning sensation were reported in group A. Conclusion: When employed as a combination therapy in the initial management of people with OSMF, curcumin can help patients with their clinical symptoms. Future research is recommended to use larger samples and longer treatment follow-up periods.